1994
DOI: 10.1128/jb.176.3.861-870.1994
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of enterobacterial pldA genes encoding outer membrane phospholipase A

Abstract: The pid4 gene of Escherichia coli encodes an outer membrane phospholipase A. A strain carrying the most commonly used mutant pkld allele appeared to express a correctly assembled PldA protein in the outer membrane. Nucleotide sequence analysis revealed that the only difference between the wild type and the mutant is the replacement of the serine residue in position 152 by phenylalanine. Since mutants that lack thepld4 gene were normally viable under laboratory conditions and had no apparent phenotype except fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(86 citation statements)
references
References 56 publications
0
86
0
Order By: Relevance
“…The rather hydrophilic character and the lack of long hydrophobic amino acid stretches, indicated that the interaction of OMPLA with the membrane di¡ered from integral membrane proteins such as bacteriorhodopsin [7]. Circular dichroism (CD) measurements indicated a high L-strand content [26] and this led Brok et al [27] to propose a molecular model with a L-barrel architecture. Electron crystallography con¢rmed the L-barrel character; projection maps showed an oval ring-like density large enough to accommodate 12 L-strands.…”
Section: Foldmentioning
confidence: 99%
See 2 more Smart Citations
“…The rather hydrophilic character and the lack of long hydrophobic amino acid stretches, indicated that the interaction of OMPLA with the membrane di¡ered from integral membrane proteins such as bacteriorhodopsin [7]. Circular dichroism (CD) measurements indicated a high L-strand content [26] and this led Brok et al [27] to propose a molecular model with a L-barrel architecture. Electron crystallography con¢rmed the L-barrel character; projection maps showed an oval ring-like density large enough to accommodate 12 L-strands.…”
Section: Foldmentioning
confidence: 99%
“…This suggested that a serine might be a catalytic residue. Later, the ¢nding of an inactive Ser152Phe variant of OMPLA suggested that residue 152 was the active site serine [27]. This hypothesis was rejected, however, when site directed mutagenesis demonstrated some tolerance at this position (Ser152Asn and Ser152Thr) [32].…”
Section: Active Sitementioning
confidence: 99%
See 1 more Smart Citation
“…It is obvious that the E. coli OMPLA and all other membrane phosphotipases, embedded in their own substrate, require a very strict regulatory mechanism for their enzymatic activity to prevent unwanted lysis of the cell envelope. In normally growing cells OMPLA seems to be dormant and E. coli mutants missing the pldA gene are normally viable under laboratory conditions, which suggests that the protein has no essential role [6]. Nevertheless, OMPLA might be important for growth of the bacteria *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…in their natural environment since it occurs widespread and is well-conserved among Enterobacteriaceae, including pathogenic species [6].…”
Section: Introductionmentioning
confidence: 99%